(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the laboratory activities that affect students’ competencies by assessing BSHM Program Facilities in Bestlink College of the Philippines. The Hospitality Management Industry comes with many exciting and even challenging opportunities that require a certain set of skills as well as managerial knowledge. The results of this study reveal that the majority of the respondents are 34 students in their 4th year, mostly male, with 53% out of 100 responses, while 47% are female. It reveals that the assessment of BSHM laboratory facilities was evaluated as “strongly agree” in terms of the front office, cookery, bread and pastry, and bartending, while housekeeping was evaluated as “agree.” The biggest challenge encountered when using the facility was distraction; in terms of students’ competencies such as knowledge, skills, and attitudes, it shows as “strongly agree.” Based on the gathered data and conclusion drawn, this study recommended to the administration and students that students should actively participate in all the training and laboratory activities from school that can help them to their competency and avoid distractions during their laboratory activity; the school administration must implement strict rules and regulations during laboratory activities, and the students should apply the scholarship to lessen their school expenses, especially for laboratory activities.